Relationship between power and sprint freestyle swimming - Sharp, R. L.; Troup, J. P.; Costill, D. L. (Medicine & Science in Sports & Exercise, 1982)
Competitive swimmers (22 females, 18 males) were tested for arm power using an isokinetic swim bench at varying velocities that covered the range required for swimming. Subjects also performed a series of 25-yard freestyle sprints. The mean power of one maximal pull on the bench at a velocity of 2.66 meters per second was measured while the average swimming time was 1.81. The correlation coefficient between the two was .90. An added study used four untrained subjects. Power improvements of 19% and sprint swimming improvements of 4% were demonstrated. This suggests that sprint swimmers could improve performance by increasing arm power. It should be noted that this study focused on 25 yards of swimming, an event that is not in the competitive schedule. Other studies by these same authors show that the relationship of strength to swimming diminishes rapidly as the distance increases.